TEKANAN DARAH PADA REMAJA. APAKAH STATUS GIZI DAN AKTIVITAS FISIK MEMILIKI KORELASI? - Arifin, Hasriany; Kalsum, Umi; Kamaruddin, Mustamir; Safitry, Rusni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Hypertension is one of the most common health problems and a major concern in public health. Based on the results of a survey conducted at SMA Negeri 7 Samarinda, it was found that there were a number of students with poor nutritional status and low levels of physical activity, both of which are potential risk factors for increased blood pressure. The purpose of this study was to determine the relationship between nutritional status and physical activity with blood pressure in adolescents. The research design used in this study was cross-sectional. The study was conducted at SMAN 7 Samarinda in October 2025. The study population consisted of all 12th grade students, with a sample size of 56 respondents. The sampling technique used was simple random sampling. The research instrument used was a research questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed a relationship between nutritional status (p value: 0.045) and physical activity (p value: 0.004) with blood pressure in adolescents. It is recommended that adolescents with a nutritional status category of “not more” and a blood pressure category of “normal” maintain a healthy lifestyle by consuming nutritious foods and maintaining a balance of physical activity.Keywords: Physical Activity, Adolescents, Static Nutrition.